ELASTISITAS PENAWARAN DAN PERUBAHAN HARGA KARET ALAM DI INDONESIA - Rayhanah, Hamidah; Harli, Nurlina; Alfarizi, Fakhri (JURNAL ILMIAH AGRITAS, 2024)
Natural rubber constitutes a significant sector within the Indonesian economy, serving as a notable source of foreign exchange through exports. Recent data indicate a decline in Indonesian rubber exports from 2018 to 2022. This study aims to assess the elasticity of supply alongside fluctuations in rubber prices in Indonesia. Employing secondary data from print and online publications provided by the Central Statistics Agency (BPS) and Gapkindo (Association of Indonesian Rubber Companies), the research spans a five-year period (2018-2022). The study applies technical analysis to evaluate the elasticity of natural rubber supply in relation to price changes. Findings reveal that the elasticity of rubber supply was elastic from 2018 to 2020, whereas it transitioned to inelastic from 2020 to 2022. This conclusion is drawn from both rubber export data and calculations of supply elasticity.